Methodology for Development of Pediatric Medicines for Complex Treatment of Diseases of Immune-Dependent Nature - Olga Rukhmakova; Tatyana Yarnykh; Olexander Tykhonov; Galina Melnyk (Journal of Global Pharma Technology, 2019)
The objective of the work – is to substantiate methodology for development of pediatric medicines for complex treatment of diseases of immune-dependent nature.Materials and Methods: at the first stage of research, their objective was set, its significance for science and practical pharmacy was shown. At the information search stage, the need for new children’s medicines was identified. The second stage of research involves determining the main directions of achieving the objective. The third stage is the choice and justification of means aimed at achieving the objective, namely, the objects and methods of research. The fourth stage is devoted to the complex of experimental studies on the development of pediatric medicines for complex treatment of diseases of immune-dependent nature. At the final stage of research technical conditions, relevant sections of registration dossier and projects of quality control methods for proposed medicines were developed.Results: based on the created general methodological concept of the development of pediatric medicines for complex treatment of diseases of immune-dependent nature, we have compiled a plan of experimental research, which is given in the article.Conclusion: methodology for development of pediatric medicines for complex treatment of diseases of immune-dependent nature has been substantiated.